2005
DOI: 10.1017/s1472928807000167
|View full text |Cite
|
Sign up to set email alerts
|

Formation of eye-specific retinogeniculate projections occurs prior to the innervation of the dorsal lateral geniculate nucleus by cholinergic fibers

Abstract: We compared the developmental periods in the mouse when projections from the two eyes become segregated in the dorsal lateral geniculate nucleus with the time when this nucleus becomes innervated by cholinergic fibers from the brainstem. Changes in labeling patterns of different tracers injected into each eye revealed that segregation of retinogeniculate inputs commences at postnatal day five (P5) and is largely complete by P8. Immunocytochemical staining showed that cholinergic neurons are present in the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…Initially, cholinergic fibers appear in the dorsolateral region of dLGN just beneath the optic tract, then gradually progress in a ventromedial direction to form a homogeneous plexus of fibers throughout dLGN. This is consistent with earlier studies in cat and mouse, showing a slow but steady increase in ChAT immunoreactivity with postnatal age [17, 18]. Thus, cholinergic innervation of dLGN occurs well after the establishment of the retinogeniculate pathway [1].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Initially, cholinergic fibers appear in the dorsolateral region of dLGN just beneath the optic tract, then gradually progress in a ventromedial direction to form a homogeneous plexus of fibers throughout dLGN. This is consistent with earlier studies in cat and mouse, showing a slow but steady increase in ChAT immunoreactivity with postnatal age [17, 18]. Thus, cholinergic innervation of dLGN occurs well after the establishment of the retinogeniculate pathway [1].…”
Section: Discussionsupporting
confidence: 92%
“…These projections have a substantial influence on retinogeniculate transmission, regulating the firing mode of dLGN neurons [13], establishing network states during sleep, wakefulness, and arousal [14, 15], as well as modulating visuo-motor interactions [16]. Previous immunohistochemical studies have shown a late postnatal onset for the labeling of acetylcholine synthesizing enzyme (choline acetyltransferase, ChAT) in dLGN, which increases in density over a protracted period of development [17, 18]. However, little is known about the source, trajectory, and pattern of cholinergic innervation in the developing mouse dLGN.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cholinergic projections seem to innervate somatosensory thalamic structures (e.g., VB, and posterior nucleus) before visual ones (e.g., dLGN, and lateroposterior nucleus). In ChAT‐Cre × Ai9 mice, we found that brainstem cholinergic projections are evident throughout all of VB by P0, yet dLGN remains devoid of fibers until the end of the first postnatal week (unpublished observations, see also Ballesteros et al ., ). Perhaps this sequence is related to a general principle of sensory thalamic development whereby the somatosensory system and develops sooner than the visual system (Bayer & Altman, ; O'Leary et al ., ; Schlaggar & O'Leary, ; Molnár & Blakemore, ; Henver et al ., ; Molnár et al ., ; Fox & Wong, ; Jacobs et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…While TRN does not receive direct sensory inputs from the periphery, thalamocortical projections from first‐order nuclei pass through the TRN at early perinatal ages (Mitrofanis & Baker, ), before the arrival of cholinergic projections. A similar sequence occurs in dLGN, in which the arrival and establishment retinofugal projections occurs well before the emergence of modulatory inputs from brainstem and layer VI of visual cortex (Ballesteros et al ., ; Seabrook et al ., ). Together, these observations suggest highly orchestrated development plan for thalamic circuit development in which nonvisual structures mature before visual ones, and where sensory projections are established before modulatory ones.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging and quantification of retinogenicular projections were carried out using similar procedures to those described previously (Ballesteros, et al, 2005; Huberman, et al, 2003). Briefly, raw images of green (Alexa 488, Fig.…”
Section: Methodsmentioning
confidence: 99%